The Short Run Impact of Penalty Rate Cuts on Employment Outcomes in Retail and Hospitality Sectors in Australia1. Issue 3 (23rd July 2018) - O'Brien, Martin; Markey, Raymond; Pol, Eduardo
Abstract : The issue of weekend penalty rates has been a contentious political issue in recent times. In its recent review of Modern Awards, the Fair Work Commission determined a reduction in Sunday penalty rates, arguing that this would result in increased employment and hours in Retail and Hospitality sectors. In this paper, we present a critique of the evidence before the Commission relating to employment creation. We also present survey findings of workers' employment before and after the penalty rate reform. In the short run we find that there was no discernible positive impact on affected workers' employment outcomes.